2004
DOI: 10.1002/lt.20328
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and clinical correlates of end-stage hepatitis B cirrhosis: A possible mechanism to explain the response to antiviral therapy

Abstract: In chronic liver disease associated with histological necroinflammation, clinical severity is frequently greater in those with higher grades of activity. Conventional wisdom assumes that necroinflammation is mild or absent in patients with end-stage hepatitis B virus (HBV) cirrhosis due to the frequent presence of mildly elevated aminotransferase levels, the absence of hepatitis B e antigen (HBeAg), and low or undetectable HBV deoxyribonucleic acid (DNA) levels. However, a histopathologic analysis of such pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Although the count of CD68 + CD86 + cells was higher in the lobular areas in comparison to the portal areas in both HBV-infected and control donors, this does not indicate an activation of CD68 + cells in the lobular areas in the control group as the total CD68 + cell count is also higher in the lobular areas in these individuals compared to the portal areas, and the percentage of CD68 + CD86 + cells was similar between the two areas in the control group. These results indicate a higher activation of CD68 + cells in the lobular areas compared to the portal areas of the liver during chronic HBV infection, which corroborates with the results showing that detectable serum HBV DNA is associated with lobular inflammation [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although the count of CD68 + CD86 + cells was higher in the lobular areas in comparison to the portal areas in both HBV-infected and control donors, this does not indicate an activation of CD68 + cells in the lobular areas in the control group as the total CD68 + cell count is also higher in the lobular areas in these individuals compared to the portal areas, and the percentage of CD68 + CD86 + cells was similar between the two areas in the control group. These results indicate a higher activation of CD68 + cells in the lobular areas compared to the portal areas of the liver during chronic HBV infection, which corroborates with the results showing that detectable serum HBV DNA is associated with lobular inflammation [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Chen et al 20 reported that the risk peaked at 7 log 10 copies/mL, while in a study on compensated HBV‐related cirrhosis, patients with HBV DNA >6 log 10 copies/mL had significantly increased risks of decompensation and death. HBV DNA > 6 log 10 copies/mL was also significantly correlated with histological liver damage and degree of fibrosis, which are crucial to the development of decompensation 29,30 . These findings suggest that cirrhotic patients with HBV DNA levels ≥6 log 10 copies/mL might die of liver failure or other complications before developing HCC.…”
Section: Discussionmentioning
confidence: 70%
“…However, in a retrospective analysis, Tong et al found that current treatment guidelines for chronic hepatitis B would identify only 20%‐60% of the patients who ultimately developed HCC, and only 27%‐70% of patients who died of non‐HCC liver‐related deaths for antiviral therapy 74. Sigal et al also found no correlation of inflammatory activity with clinical, biochemical, or virological parameters 75. Although patients with persistently elevated ALT levels (>70 U/L) may have progression of fibrosis by one stage within 4‐5 years of follow‐up,76 others have shown that up to 30% of patients with persistently normal ALT levels may also have significant fibrosis (stage 2‐4), can be at increased risk of mortality and may be candidates for therapy 42, 77–81.…”
Section: Role Of Liver Biopsy In Clinical Algorithmsmentioning
confidence: 99%